Study on Optimizing Islamic Education Learning Through the Implementation of Fink’s Taxonomy - Nushrotin Wafiroh; Sumarni, Sri; Hamami, Tasman (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2026)
In religious education, evaluation only focuses on answering questions, and once again, it only focuses on the cognitive domain. Fink’s taxonomy was chosen because it integrates cognitive, affective, metacognitive aspects (learning how to learn), social dimensions, and caring in a balanced way to produce a meaningful, applicable PAI learning experience, and is able to measure not only knowledge, but also students’ caring, interaction, and reflection. The purpose of this research and article writing is to explore the development patterns of Fink’s taxonomy specifically in Islamic Religious Education (PAI) learning. This research uses the literature study method, with data sources being secondary data in the form of research results such as books, journals, articles, websites, and, other relevant materials. The data analysis technique in this research uses content analysis. The research results show that in PAI learning, Fink’s taxonomy is an innovative and highly relevant approach. This approach not only emphasizes mastery of the material cognitively but also integrates affective and metacognitive aspects so that students can learn more actively and meaningfully. This taxonomy refers to six aspects of learning, namely foundational knowledge, application, integration, human dimension, caring, learning how to learn, along with examples of its implementation in PAI learning. The limitation of this research is the still general focus on applying Fink’s taxonomy in PAI learning, resulting in general findings as well. Recommendations for future research include refining the study by referring to specific schools in various regions to obtain a more comprehensive picture of the effectiveness of implementing Fink’s taxonomy in PAI learning.